2001
DOI: 10.1002/glia.1087
|View full text |Cite
|
Sign up to set email alerts
|

Human MBP‐specific T cells regulate IL‐6 gene expression in astrocytes through cell–cell contacts and soluble factors

Abstract: One of the distinctive features of multiple sclerosis (MS) attacks is homing to the CNS of activated T cells able to orchestrate humoral and cell-based events, resulting in immune-mediated injury to myelin and oligodendrocytes. Of the complex interplay occurring between T cells and CNS constituents, we have examined some aspects of T-cell interactions with astrocytes, the major components of the glial cells. Specifically, we focused on the ability of T cells to regulate the gene expression of interleukin-6 (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…Accordingly, we suggest that T cell recruitment and Th17 polarization after IS MBP84-104 [10] relate to the concomitant increase in IL-6 expression, which we find to be T cell-independent. Th17-released IL-17 enhances the glial IL-6 production resulting in a positive feedback loop [63], thereby augmenting further the IL-17 synthesis in Th17 cells [64, 65]. While systemic T cell activation, causing demyelination, is a likely cause of pain associated with EAE [51], direct IS administration of a pure MBP84-104 peptide into an intact nerve confirms that the activity of the MBP epitopes is sufficient to induce robust and lasting pain.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we suggest that T cell recruitment and Th17 polarization after IS MBP84-104 [10] relate to the concomitant increase in IL-6 expression, which we find to be T cell-independent. Th17-released IL-17 enhances the glial IL-6 production resulting in a positive feedback loop [63], thereby augmenting further the IL-17 synthesis in Th17 cells [64, 65]. While systemic T cell activation, causing demyelination, is a likely cause of pain associated with EAE [51], direct IS administration of a pure MBP84-104 peptide into an intact nerve confirms that the activity of the MBP epitopes is sufficient to induce robust and lasting pain.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell adhesion induces IL-6 in cultured astrocytes through activation of α3β1 integrin [65]. Stretch-induced IL-6 expression in endothelial cells is mediated by α5β1 integrin [66].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, FAK-driven JNK and ERK both regulate FGF2-induced astroglial migration [70]. The NF-kappaB pathway mediates α3β1 and α5β1 integrin stimulation of IL-6 in astrocytes [65] and endothelial cells [66]. These integrins do not regulate CNTF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has previously been observed that members of the NF-kappaB, STAT, AP-1 and E2F families [30][56], IRF-1 [36], [46], [47], [57], IRF-2 [58], IRF-5 [59], IRF-8 [20], CREB [36], [46], PPARgamma and PPARalpha [60][68], SP1 [59], SP3 [69][71], RORC [72], NR4A2, TCF2 [73], ETS-1 [74] and FOXP3 [75][85] may be implicated in MS and its disease subtypes. This paper aims to complement the companion study by uncovering, thanks to combinatorial optimization and differential co-expression methods and a different focus in the analysis, transcription factors that potentially dysregulate many genes in MS.…”
Section: Introductionmentioning
confidence: 99%